EFEKTIVITAS MODEL PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATERI LISTRIK SISWA KELAS V SD - Ina Puspitasari; Ahmad Mulyadiprana; Agnestasia Ramadhani Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students often face difficulties in understanding the topic of electricity in science learning and have not demonstrated optimal critical thinking skills. This issue arises due to the learning model used, which does not provide sufficient opportunities for exploration. This study aims to determine the effectiveness of the Project Based Learning (PjBL) model on the critical thinking skills of fifth-grade elementary school students in the topic of electricity. The research employs a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The subjects consist of two classes: a control class receiving conventional instruction, and an experimental class implementing the PjBL model. The instruments used are essay and multiple-choice questions to measure students' critical thinking skills before and after the treatment. Data analysis was conducted using non-parametric techniques, including normality tests, homogeneity tests, the Mann-Whitney test, and N-Gain calculation. The results show that the experimental class experienced a significant improvement in critical thinking skills, both in essay and multiple-choice questions, compared to the control class, which showed relatively lower improvement. These findings indicate that the PjBL model is effective in enhancing students' critical thinking skills in the topic of electricity.